The Rubáiyát of Omar Khayyám : An Updated Bibliography - Coumans, Jos, 1951- (Iranian studies series (Leiden, Netherlands), 2016)
Since the collected poems of eleventh- and twelfth-century Persian philosopher Omar Khayyám were first translated into English in 1859 by Patrick Fitzgerald, the Rubáiyát has become one of the most popular books of verse in the world. In addition to English, it has been translated into Arabic, Chinese, Dutch, French, German, Hebrew, Hindi, Russian, Urdu, and many other languages. It has been published in numerous editions: precious volumes with bejeweled bindings, artist's books, scholarly and critical editions, forgeries and fake editions, making it a perfect object for both book collectors and lovers of poetry. This comprehensive volume is the first bibliography of Khayyám's classic work since the first Rubáiyát bibliography by A. G. Potter, which was published in 1929.